Institutional change in economic geography - Bathelt, Harald; Glückler, Johannes (Progress in human geography, 2013)
This paper develops a rigorous concept of institutions to investigate the interrelationships between insti-tutional and economic change from the perspective of economic geography. We view institutions neither asbehavioural regularities nor as organizations or rules, but conceive institutions as stabilizations of mutualexpectations and correlated interaction. The paper discusses how economic interaction in space is shaped byexisting institutions, how this leads to economic decisions and new rounds of action, and how their intendedand unintended consequences impact or enact new/existing institutions. The paper explores three modes ofinstitutional change – hysteresis, emergent change, and institutional entrepreneurship.